Common Rights between neighbors a comparative study between Islamic Jurisprudence and Algerian Law - Saidoun, Azzedine; Bouzidi, Kamel (The International tax journal, 2025)
Neighborhood is an essential aspect of human social life, established by both natural disposition and divine guidance. This study examines the concept of neighbors and the common rights shared among them from the perspectives of Islamic jurisprudence and Algerian law. In Islamic law, neighbors are categorized based on proximity, faith, and kinship, with rights encompassing mutual assistance, tolerance, and continuous benefit. The Qur’an and Sunnah provide a comprehensive ethical and legal framework emphasizing justice, support, and coexistence. Algerian law, influenced by these principles, regulates neighborly relations through property rights, obligations, and limits on harm, while allowing flexibility in spatial boundaries and customary practices. The study further addresses shared rights, including the right of way, highlighting differences and complementarities between the two systems. Ultimately, Islamic and Algerian legal frameworks collectively offer a model for ensuring harmonious neighborhood relations adapted to contemporary social realities.